2010
DOI: 10.1158/1078-0432.ccr-09-2469
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Pelvic Radiation, Weekly Cisplatin, and 3-Aminopyridine-2-Carboxaldehyde Thiosemicarbazone (3-AP, NSC #663249) for Locally Advanced Cervical Cancer

Abstract: Purpose: This study assessed the safety/tolerability, pharmacokinetics, and clinical activity of three times weekly i.v. 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (3-AP, NSC #663249) in combination with once-weekly i.v. cisplatin and daily pelvic radiation in patients with gynecologic malignancies. 3-AP is a novel small-molecule inhibitor of ribonucleotide reductase (RNR) and is being tested as a potential radiosensitizer and chemosensitizer.Experimental Design: Patients with stage IB2 to IVB cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 25 publications
3
109
0
Order By: Relevance
“…This clinical trial reported that 100% of patients with advanced cervical cancer exhibited a complete clinical response and remained disease-free for 18 months with the combination regimen of cisplatin, radiation, and triapine (Kunos et al, 2010). A follow-up phase II trial is currently under way.…”
Section: Tablementioning
confidence: 99%
“…This clinical trial reported that 100% of patients with advanced cervical cancer exhibited a complete clinical response and remained disease-free for 18 months with the combination regimen of cisplatin, radiation, and triapine (Kunos et al, 2010). A follow-up phase II trial is currently under way.…”
Section: Tablementioning
confidence: 99%
“…Topotecan is a promising addition to radiation and cisplatin for locally advanced cervical cancer given the overall survival benefit of topotecan in the metastatic or recurrent setting [27][28][29]. Topotecan (2 mg/m 2 ) was given together with radiation therapy and weekly cisplatin in a phase 2 trial for locally advanced cervical cancer [30].…”
Section: Novel Cytotoxic Chemotherapy Agents For Concurrent Chemoradimentioning
confidence: 99%
“…1A), has been examined in more than 20 phase I and II clinical trials for cancer treatment (Murren et al, 2003;Wadler et al, 2004;Gojo et al, 2007;Knox et al, 2007;Kunos et al, 2010). In general, studies using 3-AP report limited antitumor activity or no response (Murren et al, 2003;Wadler et al, 2004;Gojo et al, 2007;Knox et al, 2007;Kunos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In general, studies using 3-AP report limited antitumor activity or no response (Murren et al, 2003;Wadler et al, 2004;Gojo et al, 2007;Knox et al, 2007;Kunos et al, 2010). However, other studies suggest some positive results after 3-AP was coadministered with cisplatin and daily pelvic radiation in patients with locally advanced cervical and vaginal cancer (Kunos et al, 2010). The notable side effects of 3-AP include hypoxia and methemoglobinemia (Yen et al, 2004;Gojo et al, 2007;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010), which are major concerns for patients with compromised cardiopulmonary function.…”
Section: Introductionmentioning
confidence: 99%